Evaluation of seedling proline content of wheat genotypes in relation to heat tolerance (Bangladesh Journal of Botany, 2011)
Seedling of 20 wheat genotypes were grown in Phytotron at about 25 and 35°C for measuring membrane injury in per cent and seedling proline content to investigate seedling proline as screening criterion against heat stress. The wheat genotypes (Bijoy, Sufi, Kanchan, Fang 60, BAW 1059, BL 1883, BL 1022, IVT 7, IVT 8, IVT 9, IVT 10 and BAW 917) showing < 50% membrane injury were grouped as heat tolerant (HT) and the genotypes (Shatabdi, Prodip, BAW 1064, Gourab, Pavon 76, Sonora, Kalyansona and IVT 6) showing ≥ 50% membrane injury were classified as heat sensitive (HS). At high temperature (35°C) the HT genotypes produced more than double (> 200%) proline than that of 25°C but the HS genotypes produced less quantity of proline at 35°C compared to that in HT genotypes. The seedling proline content at 35°C and membrane injury (%) maintained a significant negative correlation (r = – 0.619**) across the 20 wheat genotypes tested. Key words: Membrane thermostability; Seedling proline; Heat tolerance; Wheat DOI: http://dx.doi.org/10.3329/bjb.v40i1.7991 Bangladesh J. Bot. 40(1): 17-22, 2011 (June)